Are GSTM1 Null and GSTT1 Null Risk Factor of Autism Spectrum Disorder? A Preliminary Study - Donna Hermawati; Sue-Mian Then; Tri Indah Winarni; Rahman Jamal; Sultana MH Faradz (MEDIA MEDIKA INDONESIANA, 2012)
Background: Low plasma total glutathione (tGSH) levels, elevated levels of oxidized glutathione (GSSG) and low ratios of tGSH to GSSG in autism were reported. Glutathione S-transferases (GST) are antioxidant enzymes that play important role in cellular detoxification and the excretion of environmental pollutants including heavy metals. Glutathione S-transferase mu (GSTM1) and Glutathione S-transferase theta (GSTT1) are known to be highly polymorphic. Homozygous deletions of these genes result in lack ofenzyme activity and impaired the ability to excrete metals including mercury. Combined effects of mercury (Hg) accumulation coupled with decreased levels of antioxidants (low glutathione and antioxidant enzymes) contribute to the phenotypic presentation of autism spectrum disorder (ASD). Association of GSTM1 null genotype with autism has been reported. Therefore the preliminary study was performed to investigate the role of GSTM1 null and GSTT1 null as risk factor of ASD associated with phenotype expression.Method: Fifty one ASD patients were recruited from special need & autism school and 45 controls from Semarang & Solo. Blood veins samples were collected and genomic DNA was extracted by salting-out method in CEBIOR Semarang. Genotyping for GSTM1 and GSTT1 gene was done in UMBI Malaysia. Multiplex PCR was performed and PCR products were separated on 1.2 % agarose gel, stained with ethidium bromide and visualized on UV transiluminator. GSTM1 & GSTT1 gene product is about 625 bp and 459 bp. Absence of GSTM1 and GSTT1 gene band was interpreted as GSTM1 null & GSTT1 null.Results: The frequency of GSTM1 null and GSTT1 null in ASD higher compared with control group but the difference is not statistically significant (p=0.357, OR=0.504; 95% CI 0.117-2.168 and p=0.364, OR=0.674; 95% CI 0.287-1.580). There is also no statistically different in the distribution of GSTM1 null and GSTT1 null between mild to moderately autistic and severely autistic (p=0.983, OR=0.980; 95% CI 0.158-6.095 and p=0.439, OR=1.633; 95% CI 0.471-5.656).Conclusion: GSTM1 null and GSTT1 null are not risk factor of ASD. Further investigations are needed with a bigger sample size, analyzing multiple GST genes and GST activity determination to find out the gene susceptibility of ASD and factors that contribute to the phenotype expression of ASD.Keywords: GSTM1 null, GSTT1 null, risk factor, autism spectrum disorder ABSTRAKApakah GSTM1 Null dan GSTT1 Null merupakan faktor risiko autism spectrum disorder? Studi pendahuluanLatar belakang: Pada autism ditemukan bahwa glutathion total plasma (tGSH) rendah, oxidized glutathione (GSSG) meningkat dan rasio tGSH terhadap GSSG rendah. Glutathione s-transferase (GST) merupakan enzim antioksidan yang berperan penting dalam proses detoksifikasi seluler dan ekskresi polutan lingkungan termasuk diantaranya logam berat. Polimorfisme gen GST mu (GSTM1) dan GST theta (GSTT1) cukup tinggi. Delesi homozigot gen GSTM1 dan GSTT1 yang menyebabkan berkurang sampai tidak adanya aktivitas enzim GST serta menurunnya level antioksidan berkontribusi terhadap risiko ASD. Oleh karena itu dilakukan penelitian pendahuluan untuk mengetahui hubungan antara gen GSTM1 null dan GSTT1 null sebagai faktor risiko ASD dengan ekspresi fenotip.Metode: Lima puluh satu pasien ASD dari SLB dan sekolah autis serta 45 kontrol dari Semarang dan Solo diambil darah vena, kemudian diekstraksi dengan metode salting-out diCEBIOR Semarang. Pemeriksaan genotip gen GSTM1 & GSTT1 dilakukan di UMBI Malaysia. Metode yang digunakan adalah PCR multipleks, setelah itu produk PCR dipisahkanpada 1,2% gel agarosa kemudian dicat dengan ethidium bromida dan hasilnya dilihat menggunakan transiluminator UV. Besar produk untuk GSTM1 & GSTT1 adalah 625 bp &459 bp. Tidak adanya band untuk gen GSTM1 & GSTT1 diinterpretasikan sebagai GSTM1 null & GSTT1 null.Hasil: Frekuensi gen GSTM1 null dan GSTT1 null pada ASD lebih tinggi dibandingkan kontrol tetapi tidak ditemukan perbedaan yang signifikan (p=0,357, OR=0,504; 95% CI0,117-2,168 and p=0,364, OR=0,674; 95% CI 0,287-1,580). Distribusi gen GSTM1 null dan GSTT1 null pada autis ringan sedang dan autis berat juga tidak ditemukan perbedaan yang signifikan secara statistik (p=0,983, OR=0,980; 95% CI 0,158-6,095 and p=0,439, OR=1,633; 95% CI 0,471-5,656).Simpulan: GSTM1 null dan GSTT1 null bukan merupakan faktor risiko ASD. Penelitian lebih lanjut sangat diperlukan dengan jumlah sampel yang lebih besar, analisis gen GSTmultipel dan pemeriksaan aktivitas GST untuk mendapatkan gen faktor risiko ASD dan faktor-faktor yang mempengaruhi ekspresi fenotip ASD.